Apoio e rede social de famílias de crianças com deficiências de uma cidade mineira - Castro, Gisélia Gonçalves de (2018)
The Access to a social support network afeccts the formation and structuring of the family life of a disabled child increasing the possibilities for a better life. This general work aims, based in the health promotion referential, was to analyze the support and family social support network of a disabilities children as a way of coping in the spaces of the city. In this way, it was elaborated two chapters and five scientific articles, in the form of review articles, quantitative and qualitative articles. One inquired about the sociodemographic panorama of families and the scale was applied of social support titled Social Support Survey of the Medical Outcomes Study (MOS-SSS). Finally, the interview had as a guiding question "How did you receive the diagnosis that your child was a disabled child?" The analysis of the qualitative data was done by the method of content analysis, seeking to understand the reality situated in its context passing through the phases of ordering the data, re-reading the material, organizing the reports and classifying the data into categories. The quantitative data were compiled in the Epi Info software and the results obtained were organized into tables. The specific objectives, as well as the methodology used, were adapted to each developed article. The results were related to the confrontation experienced by 20 families of a disabled child under 12 years old who were classified in two axes: network and social support of families of a disabled child and health rights of a disabled child in the city spaces. The social and network support are a leg up to face the daily difficulties of the families of a disabled child, contributing to the reduction of stresse physical and emotional overload. Health professionals, in turn, retain capabilities not only to care for, identifying signs, motor and / or physical changes, but above all to guide, to inform and be with family members to deal with their needs and demands so intense. The family itself was singled out as the main source of support. The forms and displays of affection have been present in their lives since the differential diagnosis. However, levels of emotional support were not perceived with intensity demonstrating that the need for dialogue. This demand needs to be observed in health services that attend disabilities children, sometimes organizing groups of people with common characteristics, or opening spaces for dialogues and emotional / motivational support between family members and health professionals. It is suggested to consolidate these inclusive spaces of social participation as important instances for achievement and guarantee of rights, highlighting the rights to the city and health that everyone deserves.